Mission and Creativity: Congregational Song, Localization, and Identity in the Christian Evangelical Church in Minahasa - Matt Menger (UPT Penelitian Fakultas Teologi Universitas Kristen Indonesia Tomohon, 2025)
This article explores how creativity and theological and missiological formation occur through congregational song within the Evangelical Christian Church of Minahasa (GMIM). It asks: how do social and theological systems influence the creation of congregational music in GMIM’s local context? The study uses a multidisciplinary approach to apply the Systems Model of Creativity and Optimal Distinctiveness Theory alongside constructivist grounded theory methods. Field data includes interviews, observations, and document analysis. The case study focuses on Nyanyikanlah Nyanyian Baru bagi Tuhan (NNBT), a locally produced hymnal illustrating the interaction between creative individuals, institutional structures, and theological and cultural norms. Findings show that congregational songs serve as tools for theological participation and collective identity formation. Creativity arises not in isolation but through social negotiation, balancing community belonging with distinct expression. These insights guide Christian communities seeking to cultivate creative ecosystems that shape faith, worship, and local identity.